2017
DOI: 10.1111/trf.14462
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the advantages of platelet concentrates stored at 4°C versus 22°C

Abstract: PLT counts, cellular morphologies, PLT membranes, cytoplasmic structures, aggregation rates, and hemostatic PLT function stored at 4°C for 10 to 14 days were better than those stored at 22°C for 5 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
5
17
1
Order By: Relevance
“…These findings suggest that looking at α‐synuclein concentration increases as a surrogate biomarker of changes to platelet biology in response to such technology may prove essential to determine if use of pathogen reduction leads to changes in platelets’ health. Similarly, in light of the current increased interest in using cold‐stored platelets, it would also be of interest to establish whether α‐synuclein concentration changes can also be indicative of platelet health in this setting as well. These areas should be investigated in the future studies.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that looking at α‐synuclein concentration increases as a surrogate biomarker of changes to platelet biology in response to such technology may prove essential to determine if use of pathogen reduction leads to changes in platelets’ health. Similarly, in light of the current increased interest in using cold‐stored platelets, it would also be of interest to establish whether α‐synuclein concentration changes can also be indicative of platelet health in this setting as well. These areas should be investigated in the future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of previous studies, [2224] the correction effect of PLT preservation in cold storage in the in vitro model of thrombocytopenia [25] has been verified. Thromboelastography (TEG) indices and routine blood indices were used to evaluate blood coagulation function, anemia corrective effect, and PLT counts on an in vitro model of massive blood loss and thrombocytopenia (see experimental flow chart; Fig.…”
Section: Methodsmentioning
confidence: 94%
“…[17,18,19] Some investigations reported that PLTs in whole blood stored at low temperatures could survive for 10 days in the circulation, [20,21] and could be preserved for 5 to 7 days, and 14 days in vitro. [19,22,23] The results of a series of experiments that we conducted on PLTs stored at 4°C in vitro were as follows [24] : PLTs stored at 4°C for 10 to 14 days showed better PLT count, cellular morphology, and PLT membrane structure and cytoplasm than PLTs stored at 22°C for 5 days; PLTs stored at 4°C had slower metabolism, including less production of lactic acid, slower decrease of pH, lower consumption of glucose, and a higher recovery rate of the PLT hypotonic shock reaction rate compared with PLTs stored at 22°C within the same storage period; PLTs stored at 4°C had higher degree of aggregation, a stronger hemostatic function, and a higher activation state than the latter, and could be preserved for 10 to 14 days.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of activated forms of GPIIb‐IIIa have been evaluated in different PCs using a specific antibody (PAC‐1). Results of several studies indicate that PAC‐1–positive platelets are significantly increased in different platelet products, indicating that they have been preactivated . Reduced platelet aggregation should be expected for platelet products showing an enhanced binding of PAC‐1.…”
Section: In Vitro Testsmentioning
confidence: 99%